Patient Perceptions of Diabetes Guideline Frameworks for Individualizing Glycemic Targets - Schoenborn, Nancy L. (JAMA Intern Med, 2019)
IMPORTANCE: Diabetes guidelines recommend considering specific factors, such as diabetes duration and life expectancy, to individualize treatment in older adults. These individualized glycemic targets inform decisions on whether to intensify or deintensify medication treatment plans. How older adults with diabetes perceive these factors used to individualize glycemic targets is unknown. OBJECTIVES: To examine how older adults perceive factors used in diabetes guidelines for individualizing glycemic targets. DESIGN, SETTING, AND PARTICIPANTS: A cross-sectional national survey was conducted from December 13, 2018, to January 3, 2019, of a nationally representative, probability-based online survey panel (KnowledgePanel). A total of 1364 KnowledgePanel members who were 65 years or older and had type 2 diabetes were invited to participate in the survey; 836 (61.3%) responded, and 818 (60.0%) completed the survey. MAIN OUTCOMES AND MEASURES: The study randomized participants to 2 vignettes: one about adding and the other about removing diabetes medications from treatment plans. Participants rated the importance of 7 factors (diabetes duration, established diabetes complications, other health conditions, life expectancy, risk of adverse effects, cost, and treatment effort) in these treatment decisions using binary (yes/no) responses and the best-worst scaling method to quantify the factors’ relative importance. All participants then answered questions on how different levels of each factor were associated with aggressiveness of diabetes treatment. RESULTS: The sample included 818 participants (mean [SD] age, 74.0 [6.8] years; 469 [53.7%] male; and 668 [67.7%] white). A total of 410 participants answered questions about adding medicine, whereas 408 participants answered questions about stopping medicine. Of the 7 factors to consider for adding a diabetes medication to the treatment plan, the number who deemed each factor important ranged from 197 (45.6%) to 263 (62.8%). In contrast, these same factors were considered important by only 29 (8.4%) to 146 (37.7%) of participants when deciding to stop use of a diabetes medication. In both decisions, participants perceived the risk of adverse effects as the most important factor (relative importance was 22.8 for adding a medicine and 25.0 for stopping a medicine on a ratio scale in which, for each decision, the relative importance of the 7 factors adds up to 100, with 0 indicating complete indifference and 100 complete priority). In contrast to current guideline recommendations, most participants believed that patients with longer disease duration (498 [60.1%]), more established complications (632 [75.6%]), and greater number of other health conditions (545 [67.5%]) should receive more aggressive diabetes treatment. CONCLUSIONS AND RELEVANCE: Many older adults do not place high importance on factors recommended by guidelines to individualize diabetes treatment, especially when deciding to stop use of diabetes medications. Moreover, when considering treatment aggressiveness, many older adults weighted several factors in the opposite direction than suggested by the guidelines. Individualizing diabetes care in older adults will require effective communication regarding the benefits and consequences of making changes to treatment plans.